8‐3: A Novel Degradation Compensation Method for AMOLED Panel Based on CTP Model. Issue 1 (29th May 2019) - Gao, Wenbao; Qiu, Haijun; Wang, Dawei; Feng, Youxiong; Lai, Zhengde; Wu, Baixian; Li, Suncun; Xu, Haining; Lin, Yaoming; Wu, Shike; Cao, Yajun; Lin, Yan; et al.
Abstract : This paper proposed a new compensation method to alleviate OLED burn‐in issue. The method is complemented by doing degradation level analysis based on proposed CTP model which builds the relationship between OLED decay and various influences. A compensation algorithm is applied to adjust each subpixel's gray value for eliminating image retention.